The Great Aksumite Decorated Stelae: Architectural Characteristics, Functions, and Meanings - Manzo, Andrea (Aethiopica, 2020)
The article presents a review of the architectural and iconographic features of the big decorated Aksumite stelae in the May Ḥǝǧǧa stelae field at Aksum. Their location in the urban setting of ancient Aksum is scrutinized alongside their ceremonial and ideological function. The origin and meaning of the different features and decorative patterns characterizing the stelae are focused upon. It is suggested that these attributes may reflect ideological traits regarded as crucial by the Askumite kings and the elite in the first centuries CE. Moreover, it is demonstrated how some of these features are rooted in the local traditions, while others are related to the intense interactions the ancient Aksum had with neighbouring regions, such as the Mediterranean area and South Arabia. In particular, a new interpretation is proposed for the very distinctive outline of the top of the monuments: it may have been shaped after a specific type of shield also occurring in Meroitic and Post-Meroitic Nubia. Finally, it is suggested that the role these monuments may have played in ceremonies aimed at shaping the Aksumite identity.